The Correlation between Vocabulary Mastery and Reading Comprehension - holifatuz zahro 96 (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: This present study was aimed to know the correlation between students’ vocabulary mastery and their reading comprehension. The researcher implemented quantitive approach in which correlational design was used. The total number of the sample was 33 students from the first semester students of English Department of University of Islam Malang. To obtain the data, the researcher used vocabulary test in order to know students’ vocabulary mastery and used students’ reading score which was obtained from the teacher in order to measure the students’ ability in comprehending a text. The finding of the present study showed that the r observed of the students’ vocabulary mastery and their reading comprehension was .519 with level of significant was .002 which is higher than .001 and lower than .005. It means that there is significance correlation between students’ vocabulary mastery and their reading comprehension.Keywords: Correlation, Vocabulary Mastery, Reading Comprehension